Anthropometric and Nutritional Profile of People Living with HIV and AIDS in India: an Assessment - Anand, Deepika (Medknow Publications & Media Pvt Ltd, 2014)
BACKGROUND: Importance of nutrition in human immunodeficiency virus (HIV) is well-established; however, the information regarding the diet quality of people living with HIV (PLHIV) especially in India is lacking. OBJECTIVES: The objective of this study is to assess the anthropometric and nutritional profile of Indian PLHIV. MATERIAL AND METHODS: The study was performed on 400 adult PLHIV registered at the Antiretroviral Center (ART) center in New Delhi, India. Anthropometric data including height, weight, waist, hip, mid arm, and calf circumferences, were collected; 1-day 24-h dietary recall was done to gather nutrient intake from which nutrient adequacy ratios were computed. Mini Nutritional Assessment (MNA) was also conducted. RESULTS: The mean body mass index (BMI) of the sample was 19.73 ± 3.55 kg/m(2) with around 40% having BMI <18.5 kg/m(2) . All anthropometric measurements were found to correlate positively and significantly with CD4 count (P < 0.05). The sample consumed poor quality of diet as they could not meet even the 2/3(rd) of the Indian Council of Medical Research (2010) requirements for energy, protein, calcium, iron, riboflavin, niacin, folic acid, B12, copper, and zinc. Classification of subjects according to MNA indicated that more than 50% of the sample was at-risk of malnutrition and 34% were malnourished. With 40% of sample having BMI less than normal, 50% at risk of malnutrition together with poor nutrient intakes over a long period of time could contribute to further worsening of the nutritional status. CONCLUSION: There is a need to develop a database on nutritional profile of PLHIV in India which reinforces the need for development of effective strategies to improve their nutritional status.